2020
DOI: 10.1021/acs.analchem.0c02599
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of pH-Sensitive Doxorubicin Prodrug in ZIF-8 to Enable Targeted Delivery to Solid Tumors

Abstract: The zeolitic imidazolate framework (ZIF-8), composed of zinc ion and dimethylimidazole, is widely used in drug delivery because of the easy fabrication process and the good biosafety. However, ZIF-8 suffers from low affinity to nonelectric-rich drugs and does not have surface functional groups. Here, to deliver doxorubicin (DOX) with ZIF-8 to specific target sites, DOX was first modified with a pH-sensitive linker containing two carboxyl groups to form the inactive prodrug CAD and subsequently seeded inside ZI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 29 publications
2
47
0
12
Order By: Relevance
“…When we use nanoparticles for combining EMT-targeting and conventional chemotherapy, we cannot always carry out the commonly used strategy that is the so-called “one-stop solution”, which loads two drugs in one nanoparticle at the same time [ 26 ], but need to consider taking a sequential solution strategy in terms of delivering combinational therapeutics in a single nanoparticle. Therefore, using nanoparticles for combinational therapy remains challenging.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When we use nanoparticles for combining EMT-targeting and conventional chemotherapy, we cannot always carry out the commonly used strategy that is the so-called “one-stop solution”, which loads two drugs in one nanoparticle at the same time [ 26 ], but need to consider taking a sequential solution strategy in terms of delivering combinational therapeutics in a single nanoparticle. Therefore, using nanoparticles for combinational therapy remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Except for liposomes, there are also many other functionalized nanosystems that can be used to deliver enzymes, such as polymer nanoparticles [ 23 ], polymersomes [ 24 ], mesoporous nanoparticles [ 25 ], metal-organic framework (MOF) with biomineralization [ 26 ], DNA nanoparticles [ 27 , 28 ], emulsions [ 29 ], etc. In detail, for mesoporous silica nanoparticles (MSNs), it is reported that enzymes can be loaded in the cavity of the pores in a size-selective adsorption manner [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations